Improvement of copal tapping by slicing method - Santosa, Gunawan (Universiti Putra Malaysia, 2014)
Copal is a non-wood forest product with good prospects as an export product for Indonesia. It is produced by tapping of Agathis trees. Copal is tapped from the inner bark of the tree. However, the current tapping method damages wood of the tree and decreases stumpage health and the value of the wood. Hence, a new method that minimizes wood damage was investigated. The slicing method is a tapping method that can avoid wood damage, since it only involves slicing the bark of the tree and does not touch the wood. Therefore, a healthy stumpage can be assured until the end of stand rotation. The study showed that tapping of copal by slicing method had good productivity and minimized wood damage. Further, the slope pattern used in slicing method resulted in higher productivity and was easier to implement. The optimum tapping period was 7 days, and the copal produced was of high quality, clean and easy to harvest.